2023
DOI: 10.1088/1538-3873/acdb9a
|View full text |Cite
|
Sign up to set email alerts
|

Rubin Observatory LSST Transients and Variable Stars Roadmap

Kelly M. Hambleton,
Federica B. Bianco,
Rachel Street
et al.

Abstract: The Vera C. Rubin Legacy Survey of Space and Time (LSST) holds the potential to revolutionize time domain astrophysics, reaching completely unexplored areas of the Universe and mapping variability time scales from minutes to a decade. To prepare to maximize the potential of the Rubin LSST data for the exploration of the transient and variable Universe, one of the four pillars of Rubin LSST science, the Transient and Variable Stars Science Collaboration, one of the eight Rubin LSST Science Collaborations, has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 529 publications
0
3
0
Order By: Relevance
“…9 The Rubin Observatory will not resolve the cores of GCs as has been done by HST or MUSE. However, its wide field of view, its multicolor photometry, and the 10 yr duration of Rubin LSST would allow us to identify CVs in different parts of GCs through their variability (Hambleton et al 2023), including those residing in the outskirts, where very few have been identified so far.…”
Section: Resultsmentioning
confidence: 99%
“…9 The Rubin Observatory will not resolve the cores of GCs as has been done by HST or MUSE. However, its wide field of view, its multicolor photometry, and the 10 yr duration of Rubin LSST would allow us to identify CVs in different parts of GCs through their variability (Hambleton et al 2023), including those residing in the outskirts, where very few have been identified so far.…”
Section: Resultsmentioning
confidence: 99%
“…The Large Synoptic Survey Telescope (Vera Rubin Telescope) will pursue another strategy by obtaining low-latency LCs for the whole sky (and the deep drilling field), namely, 10(3) days, but for hundreds of thousands of SNe Ia 31 (Ivezic et al 2008;LSST Science Collaboration et al 2009;Ivezić et al 2019;Hambleton et al 2023). It will observe >300,000 SNe Ia around z = 0.3-0.4 in its wide survey and >10,000 around z = 0.9-1.0 in deep fields (Rose et al 2021).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The Vera C. Rubin Observatory's Legacy Survey of Space and Time (LSST) will spend 10 yr imaging the entire southern sky to unprecedented depth (Ivezić et al 2019). LSST promises to improve cosmological constraints by an order of magnitude (The LSST Dark Energy Science Collaboration et al 2018), dramatically expand our understanding of galaxy evolution (Robertson et al 2017), unveil the transient and variable sky (Hambleton et al 2023), and provide an inventory of the solar system of unprecedented completeness (Schwamb et al 2018).…”
Section: Introductionmentioning
confidence: 99%